CHARACTERISTICS OF EFL STUDENTS RESEARCH PROPOSALS: HOW RESEARCH STUDENTS ESTABLISH THEIR RESEARCH TERRITORY - Ni Ketut Mirahayuni; Susie Chrismalia Garnida (Anaphora : Journal of Language, Literary, and Cultural Studies, 2019)
This study investigates characteristics of EFL students's academic writing, particularly students research proposals. This study aims to uncover how novice researchers introduce their research topics within the larger research area. In particular, this study focuses on how students establish their research territory in the introductory parts of their proposals. This study focuses on students knowledge and preparation for conducting scientific research and the structural characteristics of students's research proposals. The study is based in Swales(1990) CARS Model for research article organization. This descriptive qualitative study involves 136 student proposals collected from 6th semester bachelor students majoring in English who enrolled in Research of Language classes in four academic years 2014/2015, 2015/2016, 2016/2017 and 2017/2018. Analysis of students topics indicates that most students are not yet well-prepared for conducting research. Analysis of the structural characteristics of the proposal also shows that students lacked substantial knowledge on research area or disciplines as well as scientific writing, particularly research writing, that detriment their success for entering the research community. Serious pedagogical and training efforts need to be done to improve students ability and preparation for research.